The effect of traditional GOPA games on improving the physical fitness of grade v elementary school students - afriani, Rosida; Anwar, Anwar; Salahudin, Salahudin (Universitas Suryakancana, 2025)
The purpose of this studyis to determine how the traditional game dopa affects the physical fitness level of fifth-grade students at SD Negeri 30 Nitu, Kota Bima. This research uses an experimental method and applies a total sampling technique, with a sample of 17 students. The study employs a One Group Pretest-Posttest Design. The exercise program was conducted over four weeks, with sessions held twice a week. The test used to measure physical fitness was the Indonesian Physical Fitness Test (TKJI). In this study, t-test statistics were used to test the hypothesis. The results showed that the calculated t-value was -2.936 and the t-table value was 1.746, indicating that the calculated t is greater than the t-table (-2.936 > 1.746), and the significance value of 0.01 is less than 0.05 (sig < 0.05). Therefore, it can be concluded that the Gopa game has a significant effect on improving the physical fitness of students at SD Negeri 30 Nitu, Kota Bima, as the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Keywords: 1.Traditional game Gopa; 2. Physical fitness; 3. Students